Customers’ Relation Marketing and Retention of Customers in Commercial Banks: The Case of Ecobank Buea, Southwest Region of Cameroon - Dr. Momenyi Mirabel Tangmo; Dr. Emefua Rose; Dr. Tala Patience Maforche (International Journal on Integrated Education, 2022)
Customer relationship marketing as a strategic marketing concept has gained tremendous interest among researchers and practitioners in recent times. However, few empirical studies on market orientation and performance have been established in the Cameroon banking sector. The main objective of this study is to examine the effect of relationship marketing on customer retention in the Commercial Banks in Cameroon using Ecobank Buea as a case study. Data used in the study was principally primary collected through the use of structured questionnaires administered to 1,000 customers of the bank. The data was analysed through descriptive and quantitative means and in several stages. Quantitatively the study makes used of Principal Component Analysis to generate quantitative data on which the multiple regression was done. The result of the study revealed that except for communication that has positive but insignificant effects on customer retention, relationship marketing strategies particularly bonding and trust, have positive and significant influence on customer retention at Ecobank Buea. Moreover, the study finds that the trust between the customer of the bank and the bank is attributed to their past relationship with the bank while the communication link between the customer and the bank is considerable appreciated to be good although the public relations element is weak. Furthermore the study reveals that the two most appreciable aspect of relationship marketing with Ecobank Buea are trust and communication and the least applicable is measures to enhance satisfaction of customers. On the basis of this, the study recommends a policy mix involving appropriate measures to strengthen trust, bonding, commitment, communication and customer satisfaction at the bank so as to attract more customers.